2016
DOI: 10.18623/rvd.v13i27.931
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Reclamation as Strategy for Sustainability

Abstract: The environmental change by the society is recurring and has been intensified since the first civilizations. However, the lack of conservationist practices has caused the emergence of degraded areas, whose recovery is fundamental for the sustainability. In this context, this paper aims at analyzing the environmental recovery as a public policy strategy supported in the Brazilian legislation. As methodology, a documental and analytical research was developed on the regulations, discussed at a multidisciplinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Based on a review of Brazilian legislation, Bressane et al (2016) found that environmental protection is widely regulated, and represents one of the main public policy strategies adopted in the country. Despite this, the effectiveness of legal rules applied to land-use control depends on their compliance, especially in areas with high population density, as the metropolitan regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a review of Brazilian legislation, Bressane et al (2016) found that environmental protection is widely regulated, and represents one of the main public policy strategies adopted in the country. Despite this, the effectiveness of legal rules applied to land-use control depends on their compliance, especially in areas with high population density, as the metropolitan regions.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the advance in Brazilian legal framework, pointed out by these authors (Bressane et al, 2016), the present study aims to verify whether land-use has still significantly affected water quality, through a case study at metropolitan region of southeastern Brazil. In this sense, the results of the present study were discussed in comparison with the findings from the studies carried out in the same region about 10 15 years ago (Bhutiani and Khanna, 2007;Etto et al, 2013;Göransson et al, 2013;Göransson et al, 2013;Kemerich et al, 2013;Longo et al, 2012;Longo et al, 2013;Souza and Gastaldini, 2014).…”
Section: Introductionmentioning
confidence: 99%